2011
DOI: 10.1007/s13225-011-0141-x
|View full text |Cite
|
Sign up to set email alerts
|

A molecular, morphological and ecological re-appraisal of Venturiales―a new order of Dothideomycetes

Abstract: The Venturiaceae was traditionally assigned to Pleosporales although its diagnostic characters readily distinguish it from other pleosporalean families. These include a parasitic or saprobic lifestyle, occurring on leaves or stems of dicotyledons; small to medium-sized ascomata, often with setae; deliquescing pseudoparaphyses; 8-spored, broadly cylindrical to obclavate asci; 1-septate, yellowish, greenish or pale brown to brown ascospores; and hyphomycetous anamorphs. Phylogenetically, core genera of Venturiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 51 publications
6
92
0
Order By: Relevance
“…Zhang et al (2012) demonstrated that this species groups with Protoventuria alpina to form a distinct lineage of Dothideomycetes that should be regarded as Protoventuria . The type species of Ramalia, R. veronicae, was placed in the genus Fusicladium as F. veronicae by Sutton & Pascoe (1988).…”
Section: Dothideomycetesmentioning
confidence: 96%
“…Zhang et al (2012) demonstrated that this species groups with Protoventuria alpina to form a distinct lineage of Dothideomycetes that should be regarded as Protoventuria . The type species of Ramalia, R. veronicae, was placed in the genus Fusicladium as F. veronicae by Sutton & Pascoe (1988).…”
Section: Dothideomycetesmentioning
confidence: 96%
“…Most of the taxa used in this study are derived from Schoch et al (2009) and Zhang et al (2011). The LSU dataset for showing the placement of Clavatispora thailandica comprises 40 taxa including Acrospermum compressum (Acrospermales) as an outgroup (Table 1).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Morphologically it fits Barr's concept of Neocoleroa. DNA sequences from the type specimen and from cultures grown from single ascospores from the type, place this species in the Sympoventuriaceae, sister to the Venturiaceae in the Venturiales (Zhang et al 2011). …”
mentioning
confidence: 93%